2021
DOI: 10.3390/ijerph18041393
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress in Spanish Police Officers: Validating the Effort-Reward Imbalance Questionnaire

Abstract: The Effort-Reward Imbalance Questionnaire (hereinafter, ERIQ) has been largely used worldwide to assess job stress, but it has not yet been applied in Spanish police. The objective of this study was to examine the construct validity and the internal consistency of the ERIQ in police officers. A cross-sectional study was carried out, using a nonprobability sampling (quota). A total of 217 Spanish police officers participated, 192 men (88.47%) and 25 women (11.53%). The mean age was 41 years (SD = 7.51). These p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…While the Chinese health industry’s salary and welfare levels still need to be improved ( 41 ). Some studies have confirmed that the disparity between investment and return is a significant factor influencing occupational stress ( 42 ). As a result, health care managers can implement a scientific performance appraisal and salary distribution system to try to achieve a balance between effort and reward, reduce occupational stress among primary health care workers, and relieve cumulative fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…While the Chinese health industry’s salary and welfare levels still need to be improved ( 41 ). Some studies have confirmed that the disparity between investment and return is a significant factor influencing occupational stress ( 42 ). As a result, health care managers can implement a scientific performance appraisal and salary distribution system to try to achieve a balance between effort and reward, reduce occupational stress among primary health care workers, and relieve cumulative fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors point to the psychological burden posed to police officers during their work [ 53 , 54 ]. Mental workload must not be underestimated, as it may affect the police even after work [ 6 , 55 , 56 ]. Its underestimation can lead in the long run to burnout syndrome or other mental problems that negatively affect his or her quality of life [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The municipal police agencies perform tasks only in a defined territory, so their competence is not nationwide. Their police activity is converging to the police activity performed by the Police Force, as is the case in many member states of the European Union [ 4 , 5 , 6 ]. On the contrary, some member states of the European Union do not use the services of the municipal police in their metropolises [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Job stress in police officers and its consequences is attracting the attention of the scientific community both from a descriptive and preventive perspective, as well as from the point of view of intervention (Baek et al, 2021;Bhowmick and Mulla, 2021;Foley and Massey, 2021;Luceño-Moreno et al, 2021;Márquez et al, 2021). Guaranteeing fundamental rights, optimising citizen security, and protecting private property are activities that require considerable psychological effort on the part of police officers.…”
Section: Introductionmentioning
confidence: 99%